Pengaruh Profitabilitas Likuiditas dan Struktur Modal pada Perusahaan Farmasi yang Terdaftar di Bursa Efek Indonesia - Nurwani Nurwani (Jurnal Riset Akuntansi dan Bisnis, 2022)
: The purpose of this research was to examine the influence and analyze of profitability and liquidity on capital structure partially and simultaneously. The population of this research was10 pharmaceutical companies listed in the Indonesia Stock Exchange in the period of 2016-2020 and samples of 7 companies by using purposive sampling technique. The data were processed by using multiple linear regression analysis, hypothesis test, and determination test. The result of the research showed that first, profitability had influence negative and significant on capital structure. Secondly, showed that liquidity had influence negative and significant on capital structure. Thirdly, showed that profitability and liquidity influence significant on capital stucture simultaneously.